Evaluation of semen quality of endangered Caspian brown trout (Salmo trutta caspius) in different times of spermiation during the spawning season - S. Hajirezaee; B. Mojazi Amiri; A. Mirvaghefi; A. Sheikh Ahmadi (Czech Journal of Animal Science, 2010)
Sperm motility and sperm production as well as organic and inorganic components present in the seminal plasma were measured at different time periods of spermiation during the spawning season in order to evaluate the semen quality in Caspian brown trout, Salmo trutta caspius. For such evaluation, males were divided into four groups based on the date of spermiation: group A (pre-mature broodstocks), group B and C (mid-mature broodstocks), group D (late-mature broodstocks). Our results showed that the Caspian brown trout produces semen of variable quality depending on the date in the period of spermiation. In this regard, the percentage of motile spermatozoa, duration of motility, sperm density, osmolality and also the concentrations of Na+, Cl-, K+, Ca2+, Mg2+ and total protein content were significantly higher in mid-mature broodstocks (which matured in the middle of spawning season, i.e. groups B and C) compared to pre-mature (group A) and late-mature (group D) samples. Statistically significant positive correlations were also found between these semen parameters: sperm production vs Na+, Cl-, K+, Ca2+, Mg2+, total protein, osmolality, pH; percentage of motile spermatozoa vs Na+, Cl-, K+, Ca2+, Mg2+, total protein, osmolality; duration of motility vs Na+, Cl-, K+, Ca2+, Mg2+, total protein, pH. The significance of such correlations is interpreted in terms of physiological implications and is discussed in relation to semen quality.